5 PEMBERDAYAAN PEREMPUAN DALAM MEMPERKUAT PEREKONOMIAN LOKAL BERBASIS UMKM - Wahyu Indah Sari; Nasution, Lia Nazliana; Syaad Afifuddin; Anwar Suhut (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2026)
Women play a strategic role in sustaining household livelihoods and strengthening local economies in coastal areas. This community service program aims to empower women entrepreneurs through strengthening micro, small, and medium enterprises (MSMEs) based on local wisdom in Desa Kota Pari, Pantai Cermin District. Most women in this coastal village are involved in home-based economic activities such as traditional food processing, fisheries-based products, and small-scale trading. However, limited financial literacy, income management, and market access constrain business development. The program was implemented through observation, counseling, participatory discussions, and evaluation. The results show improved understanding of income management, increased awareness of business sustainability, and strengthened economic roles of women entrepreneurs. This program confirms that empowering women through MSMEs contributes significantly to strengthening local economic resilience in coastal communities.